The Influence of Pantograph Carbon–Metal Composite Slider Thermal Properties on the Railroad Wire Temperature - Adam Mańka; Andrzej Hełka; Janusz Ćwiek (Energies, 2021)
This article presents the methodology, description, and results of experimental studies aimed at determining the impact of the copper concentration in a carbon–metal composite contact strip on the maximum temperature of the copper contact wire during a contact event when used for operation in the railway industry in Europe. Based on these tests, we determined the minimum percentage of copper that is required for the composite to meet the normative requirements for current loads. In addition to experimental research, a 3D FEM numerical model was also developed in which the contact strip and contact wire geometry were mapped, along with imposed loads resulting from the test for current loads mentioned above. Fifteen simulation variants were carried out for the established model, where the value of the thermal conductivity coefficient and the specific heat coefficient were varied. On this basis, we analyzed the sensitivity of thermal coefficients to the contact wire temperature and determined the minimum conductivity coefficient value, which allowed the maximum copper contact wire temperature of 120 °C to be obtained during the verification tests.